Diastereoselective Synthesis of 2,6-Disubstituted 4-(Dimethoxymethyl)tetrahydropyrans Using TMSOTf-Promoted Prins–Pinacol Cyclization - Kim, Young Seub; Lee, Jae Kyun; Pae, Ae Nim; Cho, Yong Seo; Min, Sun-Joon (Synlett, 2013)
We have described a highly diastereoselective synthesis of 2,6-disubstituted 4-(dimethoxymethyl)tetrahydropyrans via TMSOTf-promoted Prins–pinacol reaction of methylene diol with acetals. This reaction provides an efficient procedure to synthesize functionalized tetrahydropyrans containing an acetal group at the C4 position with all-cis 2,4,6 relative configuration.
Keywords: cyclization; Lewis acids; oxonium ion; diastereoselectivity; 2,4,6-trisubstituted tetrahydropyrans